1998
DOI: 10.1161/01.hyp.31.1.349
|View full text |Cite
|
Sign up to set email alerts
|

AT 2 Receptor Stimulation Increases Aortic Cyclic GMP in SHRSP by a Kinin-Dependent Mechanism

Abstract: Abstract-In the present study we tested the hypothesis whether an anglotensm AT, receptor-mediated stlmulatlon of the bradykmm (BK)/mtnc oxide (NO) system can account for the effects of AT1 receptor antagonism on aortlc cGMP described previously m SHRSP Adult SHRSP were treated for 4 hours with anglotensm II (ANG II) (30 rig/kg per mm IV) or vehicle (0 9% NaCl IV) Animals were pretreated with vehicle, losartan (100 mg/kg PO), PD 123319 (30 mg/kg IV), losartan plus PD 123319, lcatlbant (500 @g/kg IV), NG-mtro-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
209
4
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(246 citation statements)
references
References 28 publications
31
209
4
2
Order By: Relevance
“…BK seems to play an important role in the vascular effects of Ang II (Seyedi et al, 1995;Gohlke et al, 1998;Tsutsumi et al, 1999;Sosa-Canache et al, 2000;Katada & Majima, 2002). Probably, the vasodilator effect of Ang II in the rat MVB is modulated by BK mechanisms, since we showed that captopril enhanced the vasodilator effects of BK and Ang II.…”
Section: Rs De Moura Et Al Angiotensin Ii-dependent Vasodilation 863supporting
confidence: 51%
“…BK seems to play an important role in the vascular effects of Ang II (Seyedi et al, 1995;Gohlke et al, 1998;Tsutsumi et al, 1999;Sosa-Canache et al, 2000;Katada & Majima, 2002). Probably, the vasodilator effect of Ang II in the rat MVB is modulated by BK mechanisms, since we showed that captopril enhanced the vasodilator effects of BK and Ang II.…”
Section: Rs De Moura Et Al Angiotensin Ii-dependent Vasodilation 863supporting
confidence: 51%
“…Recent studies have shown that stimulation of the AT 2 receptor increases the production of bradykinin, PGE 2 and NO, leading to arteriolar vasodilation and suppression of cell growth and proliferation. [40][41][42][43] Therefore, the inability of ARBs to prevent kinin degradation in contradistinction to ACE inhibitors is compensated by their ability to increase kinin production through the AT 2 receptor. Although these actions are shared by all ARBs, telmisartan has the additional advantage of being longer acting and more efficacious with respect to its antihypertensive effects and to effectively suppress the rise of blood pressure during the early hours of the morning when it is needed the most.…”
Section: Angiotensin Receptor Blockers Vs Angiotensin-converting Enzymentioning
confidence: 99%
“…Part of this effect may be due to an AT 2 -mediated stimulation of tissue nitric oxide (NO) and cGMP levels. 69 Despite the success of ACE inhibitors in the clinical management of cardiovascular disease, mortality remains high in patients with chronic heart failure. This may be due, in part, to the ACE-independent pathways for angiotensin II formation.…”
Section: At 1 -Receptor Blockade Of Rasmentioning
confidence: 99%